What Can the Price Gap between Branded and Private Label Products Tell Us about Markups? - Robert Barsky; Mark Bergen; Shantanu Dutta; Daniel Levy (Bar-Ilan University, Department of Economics, 2002)
In this paper we investigate the size of markups for nationally branded products sold in the U.S. retail grocery industry. Using scanner data from a large Midwestern supermarket chain, we compute several measures of upper and lower bounds on markup ratios for over 230 nationally branded products in 19 categories. Our method is based on the insight that retail and wholesale prices of private label products provide information on marginal costs that are also applicable to the appropriately matched nationally branded products. Under reasonable assumptions - the accuracy of which we consider in some detail – the wholesale price of a private label product is an upper bound for the marginal manufacturing cost of its nationally branded equivalent, while the retailer's margin on the national brand is an upper bound on the retailer's marginal handling cost for both the brand and private label versions. We find that lower bounds on the “full” markup ratio range from 3.44 for toothbrushes and 2.23 for soft drinks to about 1.15-1.20 for canned tuna and frozen entrees, with the majority of categories falling in the range 1.40-2.10. Lower bounds on manufacturers' markups are even higher. Thus the data indicate that markups on nationally branded products sold in U.S. supermarkets are large.In this paper we investigate the size of markups for nationally branded products sold in the U.S. retail grocery industry. Using scanner data from a large Midwestern grocery chain we compute upper and lower bounds for the “true” markup ratio for over 230 nationally branded products in 19 categories. Our method is based on the insight that retail and wholesale prices of private label products provide information on marginal costs of nationally branded products as well. The data include not only the prices and quantities sold by UPC, but also the retailers' margins on each product, which allow us to measure the markup ratios for nationally branded product manufacturers using both wholesale and retail prices. We find that lower bounds on markup ratios measured this way range from 3.44 for toothbrushes and 2.23 for soft drinks to about 1.15–1.20 for canned tuna and frozen entrees, with the majority of categories falling in the range 1.4–2.10. Thus the data indicate that markups on nationally branded products sold in U.S. supermarkets are large.
Keywords: D4; E3; L1; L8; 330; markup; retail and wholesale price; marginal cost; national brand; private label